CHEMICAL CONSTITUENTS FROM THE MYCELIA OF ANTRODIA CINNAMOMEA - WU,MING-DER (Sociedad Chilena de Química, 2007)
The mycelia of Antrodia cinnamomea (BCRC 36799) were extracted and four compounds were purified: one new benzoquinone, 5-methyl-benzo[1,3]dioxole-4,7-dione (1), one new benzenoid, isobutylphenol (2), along with two known benzoquinone derivatives, 2,3-dimethoxy-5-methyl[1,4]benzoquinone (3), 2-methoxy-5-methyl[1,4]benzoquinone (4). Their structures were elucidated by intensive MS and 2D NMR study. These compounds were evaluated for their antioxidant activities in the 1,1-diphenyl-2-picrylhydrazyl (DPPH) and supero xide radical scavenging assay. Preliminary antioxidant activity data revealed that compound 4 showed a poor radical scavenging activity